The Partisan Counter-Archive: Retracing the Ruptures of Art and Memory in the Yugoslav People’s Liberation Struggle by Gal Kirn; a review by Naum Trajanovski - Journal for Politics, Gender; Culture, Identities; Trajanovski, Naum (Identities: Journal for Politics, Gender and Culture, 2021)
Author(s): Naum Trajanovski Title (English): A Review of the Partisan Counter-Archive: Retracing the Ruptures of Art and Memory in the Yugoslav People’s Liberation Struggle by Gal Kirn Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 18, No. 1-2 (2021). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 106-108 Page Count: 3 Citation (English): Naum Trajanovski, “A Review of the Partisan Counter-Archive: Retracing the Ruptures of Art and Memory in the Yugoslav People’s Liberation Struggle by Gal Kirn,” Identities: Journal for Politics, Gender and Culture, Vol. 18, No. 1-2 (2021): 106-108. Author Biography Naum Trajanovski, Graduate School for Social Research, Institute of Philosophy and Sociology, Polish Academy of Sciences. Naum Trajanovski (Graduate School for Social Research, Institute of Philosophy and Sociology, Polish Academy of Sciences) is a PhD candidate at the GSSR. He was a project co-coordinator at the European Network Remembrance and Solidarity (2017) and a researcher at the Faculty of Philosophy, Ss. Cyril and Methodius University – Skopje (2018-2020). His major academic interests include memory politics in North Macedonia and sociological knowledge transfer in 1960s Eastern Europe. He authored several papers and a monograph, in Macedonian, on the memory politics in the state after 1991.